Performing the Pandemics - Jorge Poveda Yánez; María José Bejarano Salazar; Naiara Müssnich Rotta Gomes de Assunção; Subhashini Goda Venkataramani (Dance Articulated, 2021)
Stemming from one creative experience that emerged in London during the lockdown period of early 2020, called the “Emergency Festival”, this article is a result of observations based on practice, centred around the festival that a group of multicultural, interdisciplinary movement-based researchers and dancers created, curated, and participated in. It explores the possibility of making a radical alterity out of a hitherto previously established ideas of territory, time, and community, using performative writing as practice-based analysis scheme. Employing the concept of “communitas” by Victor Turner (1969) to approach the phenomenon of dance through distance, the article examines the importance of the emergence of collaboration as a way forward, epistemologically looking at dance as a method of creating and sustaining communities that are longing for a sense of home in times of change. The writing is divided into three parts, focussing on the aspects of space, time, and community, all the while embedded in the nature of movement and its effect on the practitioners, and onlookers, concluding with contemplation on the place of dance in varied mediums and the way forward to study it in a period of global disruption.